A Competent Approach to Teaching Probability Theory and Mathematical Statistics (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article examines the competence issues, problems and proposals for teaching probability theory and mathematical statistics in higher education institutions.